KNOWLEDGE AND ATTITUDE ON THE ROLE OF PHYSIOTHERAPY IN THE INTENSIVE CARE UNIT AMONG OTHER HEALTH CARE PROFESSIONALS IN SOUTH EAST, NIGERIA - Okonkwo, Arinze Christian; Ogbonna, Cynthia; UMUNNAH, Joseph Onuwa; Chukwuemeka, Uche (Journal of Biomedical Investigation, 2023)
Background: The Intensive Care Unit (ICU) is designed to ensure that continuous and comprehensive care is delivered to patients by highly trained staff and should include both clinically oriented and design based multi- professional team members. Aim: This study set in South East Nigerian States, was therefore aimed to determine the knowledge and attitude of the role of physiotherapy in the ICU among other HCPs in South East Nigeria; and the influence of selected socio-demographic profile of the participants on the constructs. Methods: A cross-sectional survey involving Sixty (60) conveniently sampled HCPs working in the ICU who consented and participated. The participants' socio-demographic variables were obtained and a questionnaire was used to evaluate the knowledge and attitude of the role of physiotherapy in ICU among other HCPs in south east Nigeria. The obtained data were summarized using descriptive statistics of frequency, percentages, mean, and standard deviation, while inferential statistics of Mann Whitney U test, Kruskal Wallis test, and Spearman-rank correlation were used to analyze data with the alpha set at <0.05. Results: The majority of the participants (66.6%) had an acceptable level of knowledge, while all the participants (100%) had a positive attitude. No significant correlation was found between knowledge and attitude (rho=0.026, P=0.844). Age had a significant influence on attitude (P =0.003), but not on knowledge (P = 0.208). Gender did not significantly influence knowledge (P= 0.127) and attitude (P =0.208). Educational qualification had no significant influence on knowledge (P=0.212) and attitude (P =0.05). Profession significantly influenced attitude (P =0.04) but not knowledge (P=0.383). The clinical experience had a significant influence on attitude (P <0.0001) but not on knowledge (P=0.594). Conclusion: Health Care Professionals working in ICU had an acceptable level of knowledge and a positive attitude regarding physiotherapy involvement in the ICU.